A description of Macrobiotus horningi sp. nov. and redescriptions of M. maculatus comb. nov. Iharos, 1973 and M. rawsoni Horning et al., 1978 (Tardigrada: Eutardigrada: Macrobiotidae: hufelandi group) - Kaczmarek, Łukasz; Michalczyk, Łukasz (Zootaxa, 2017)
We examined microscope slides from Horning and Iharos tardigrade collections from Museum of New Zealand Te Papa Tongarewa in Wellington and Hungarian Natural History Museum in Budapest with species of the Macrobiotus hufelandi group. Based on this material we describe one new species, Macrobiotus horningi sp. nov., and re-describe two others, M. maculatus comb. nov. Iharos, 1973 and M. rawsoni Horning et al., 1978. With the oral cavity armature of the patagonicus type and chorion of the hufelandi type, Macrobiotus horningi sp. nov. is most similar to: M. personatus Biserov, 1990, M. sandrae Bertolani & Rebecchi, 1993, M. serratus Bertolani et al., 1996, M. sottilei Pilato et al., 2012, M. terminalis Bertolani & Rebecchi, 1993 and M. vladimiri Bertolani et al., 2011, but it differs from them in morphological and morphometric traits. With eggs of the maculatus type, M. maculatus comb. nov. is most similar to: M. biserovi Bertolani et al., 1996, M. denticulatus Dastych, 2002, M. macrocalix Bertolani & Rebecchi, 1993 and M. ramoli Dastych, 2005, but differs from them in morphological and morphometric characters.